Pedagogia Waldorf : entre trajetórias formativas e experiências de alunos egressos do ensino fundamental - Paula, Helena Maria Rodrigues de (2021)
The Waldorf Pedagogy presents itself as a humanist and holistic pedagogical proposal, which concentrates its efforts in the education of the human being respecting the phases of his development. Its focus is not a content-based education, neither consumerist nor immediatist. Such characteristics still generate a lot of questionings if the students can really learn and if they can adapt themselves in other pedagogical proposals. Therefore, the present research had as aim to identify how the egressed from an Elementary School, that adopts as formative pedagogical presupposition the Waldorf Pedagogy, in Cuiabá, carried out their trajectory in the High School, the admission in the university and which were the formative contributions or fragilities identified in this process. To do so, it was carried out a bibliographic research that treated the bases of Anthroposophy, of Waldorf Pedagogy, its historical origin and the fundaments that sustain the curriculum organization. On the other hand, the methodology adopted to do the research took over the condition of qualitative approach, with the descriptive type, having as subjects students egressed from Elementary Education of a school that adopts the Waldorf Pedagogy and the fathers, mothers and/or responsible for these students. These subjects participated of the research through a structured interview done with virtual platforms. From the data produced, it was possible to consider that the students egressed from the Waldorf Pedagogy can have a good performance when changing pedagogical proposal, even though they go through a period of adaptation. According to the manifestations of the interviewees, the Waldorf education contemplates the academic, social and emotional formation, contributing positively to a responsible and individually and collectively aware posture.